2019
DOI: 10.1021/acs.organomet.9b00636
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Chemistry of Metal Organic Compounds Adsorbed on Oxide Surfaces

Abstract: The thermal chemistry of several metal organic compounds with amidinate, diketonate, or cyclopentadienyl (Cp) ligands on oxide surfaces, mainly on silicon dioxide but also on aluminum oxide, was studied by using surface sensitive techniques, including temperature-programmed desorption (TPD), X-ray photoelectron spectroscopy (XPS), reflection–absorption infrared spectroscopy (RAIRS), and static secondary ion mass spectrometry (SSIMS), and those studies were complemented with quantum mechanics calculations. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 144 publications
1
18
0
Order By: Relevance
“…It is experimentally known that, during the adsorption and dissociation process of copper­(I)– N , N ′ dimethylacetamidinate on metal surfaces, the Cu atoms from the precursor become reduced to their metallic state. ,,,,, It is also evident from those experimental studies that the rate-limiting step is the activation of the ligands, as the temperature threshold for Cu reduction and acetamidinate dehydrogenation is approximately the same. ,, It would be valuable to determine exactly at what stage of the conversion this metal reduction occurs. To that end, we have mapped here the evolution of the charges associated with the key elements of the system upon adsorption and dissociation of the dimer on the Ni(110) surface using Bader’s charge population analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is experimentally known that, during the adsorption and dissociation process of copper­(I)– N , N ′ dimethylacetamidinate on metal surfaces, the Cu atoms from the precursor become reduced to their metallic state. ,,,,, It is also evident from those experimental studies that the rate-limiting step is the activation of the ligands, as the temperature threshold for Cu reduction and acetamidinate dehydrogenation is approximately the same. ,, It would be valuable to determine exactly at what stage of the conversion this metal reduction occurs. To that end, we have mapped here the evolution of the charges associated with the key elements of the system upon adsorption and dissociation of the dimer on the Ni(110) surface using Bader’s charge population analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, the advance of density functional theory (DFT) provides an alternative way to get that information. We , and others , have embarked in complementing studies on the mechanism of metalorganics on surfaces with this type of theoretical approach.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most of these compounds, the ligands are bound to the Ni centers in a bidentate configuration, a type of complexation that confers additional stability and presumably minimizes detrimental side decomposition pathways that may lead to the deposition of undesirable impurities. Nevertheless, recent surface-science studies by us and others have shown that even with bidentate ligands there are chemical avenues on solid surfaces for the organic moieties to fragment and leave carbon and other elements behind. In order to optimize the synthesis of metal organic precursors for ALD it is important to block these side reactions, and that in turn requires a better understanding of the fundamental mechanism of the thermally activated reactions that different types of organic ligands can follow when adsorbed on surfaces.…”
Section: Introductionmentioning
confidence: 99%